2016
DOI: 10.1111/jop.12406
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1‐Smad3‐Jagged1‐Notch1–Slug signaling pathway takes part in tumorigenesis and progress of tongue squamous cell carcinoma

Abstract: The key protein expression in TGFβ1-Smad3-Jagged1-Notch1-Slug signaling pathway significantly correlated with the clinicopathological features of TSCC patients. It's potential as a biomarker and a novel therapeutic target for TSCC patients at risk of metastasis. It may play an irreplaceable role in TSCC progression which may attribute to promoting EMT which enhances cell migration, invasion and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
1
17
0
8
Order By: Relevance
“…Nearly 50% of OTSCC patients have lymph node metastases, indicating that OTSCC cells have strong invasive and migratory capacities. For cellular progression, epithelial cancer cells must undergo increased invasive and migratory abilities during EMT, which is an essential step for metastatic spreading (19,20). EMT is a multi-step process where epithelial cells acquire a mesenchymal phenotype which is characterized by enhanced motility ability, downregulation of epithelial proteins including E-cadherin, claudins and α-catenin, and overexpression of mesenchymal phenotype proteins, such as vimentin, N-cadherin and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 50% of OTSCC patients have lymph node metastases, indicating that OTSCC cells have strong invasive and migratory capacities. For cellular progression, epithelial cancer cells must undergo increased invasive and migratory abilities during EMT, which is an essential step for metastatic spreading (19,20). EMT is a multi-step process where epithelial cells acquire a mesenchymal phenotype which is characterized by enhanced motility ability, downregulation of epithelial proteins including E-cadherin, claudins and α-catenin, and overexpression of mesenchymal phenotype proteins, such as vimentin, N-cadherin and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is composed of αβ heterodimers; expression of the α-subunit is tightly regulated by oxygen, whereas the β-subunit is constitutively expressed (18). Numerous studies have shown that HIF-1α overexpression is frequently observed in human cancers and is associated with metastasis of several types of solid types of carcinoma, including breast carcinoma, chondrosarcoma, colorectal adenocarcinoma and head and neck cancer (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Tongue squamous cell carcinoma (TSCC) was the most frequent type of oral squamous cell carcinoma (OSCC) and was famous for its high ability of metastasis and proliferation . TSCC usually leads to dysfunction of speech, mastication and deglutition .…”
Section: Introductionmentioning
confidence: 99%
“…The TGF- β 1/smad3 signaling pathway, a critical regulator of apoptosis, mediates important biological processes including tumorigenesis [ 38 ]. Yu et al [ 39 ] reported that genistein inhibits mouse colon cancer via regulating TGF- β 1/smad pathway.…”
Section: Discussionmentioning
confidence: 99%